Let $X_1$, $X_2$ be iid random variables.

How do I show that for non-negative variables $E(|X_1 - X_2|)$ is bound from above by twice the expected value of $X_1$ (or $X_2$)?

  • $\begingroup$ Clearly this is not true when the common expectation is not positive! $\endgroup$
    – whuber
    Jan 5, 2018 at 14:41
  • 2
    $\begingroup$ yes thats why I wrote "nonnegative variables" $\endgroup$
    – Manuel R
    Jan 5, 2018 at 15:32
  • $\begingroup$ Simply apply the triangle inequality. $\endgroup$
    – Zhanxiong
    Jan 5, 2018 at 15:54
  • 3
    $\begingroup$ $|X_1-X_2| \leq |X_1| + |X_2|$. You actually don't need the independence assumption to reach your conclusion. $\endgroup$
    – Zhanxiong
    Jan 5, 2018 at 15:58
  • 1
    $\begingroup$ @Manuel S, I added a self-study tag to the post. $\endgroup$ Jan 5, 2018 at 16:39

1 Answer 1


as pointed out in the comments by @zhanxiong, the triangle inequality is sufficient here, take:

$|X_1 -X_2| \leq |X_1| +|X_2|$ and take expectations to get

$\mathbb{E}(|X_1 -X_2|) \leq \mathbb{E}(|X_1|) +\mathbb{E}(|X_2|)$. However, you cannot equate the two marginal expectations to be the same value without assuming they have the same marginal distributions. Assuming this you can conclude $\mathbb{E}(|X_1 -X_2|) \leq 2\mathbb{E}(|X_1|)$ and the non-negative assumption allows you to say that $\mathbb{E}(|X_1|) = \mathbb{E}(X_1)$. So that if $\mu=\mathbb{E}(X_1)$ then you have: $\mathbb{E}(|X_1 -X_2|) \leq 2\mu$.

As mentioned by @zhanxiong in the comments this doesn't use independence but does use that the marginals have the same distributions.

As @whuber points out in a comment this is not possible if the variables could be negative. Here is a simple example showing what happens if they are negative expectations; let $X_i \sim Rademacher(p=1/3)$ where $\Pr(X_i=1)=1/3$ and $\Pr(X_i=-1)=2/3$. The expectation of each is $\mathbb{E}(X_i) =-1/3$. Then with the i.i.d. assumption we can calculate the four probabilities:

  1. $\Pr(X_1=1, X_2=1) = 1/9$ and $|1-1| = 0$
  2. $\Pr(X_1=1, X_2=-1) = 2/9$ and $|1-(-1)| =2$
  3. $\Pr(X_1=-1, X_2=1) = 2/9$ and $|-1-1| =2$
  4. $\Pr(X_1=-1, X_2=-1) = 4/9$ and $|-1-(-1)|=0$

Multiplying the probabilities of each event (l.h.s.) with the values on the r.h.s. and summing all four numbers gives you $\mathbb{E}(|X_1 -X_2|)=8/9$ and twice the expectation is: $2\mathbb{E}(X_i) = -2/3$. Clearly, $8/9 \nleq -2/3$ so the claim needs additional conditions/assumptions (non-negativity) to be true.

  • $\begingroup$ I'm curious, why did you chose that particular Rademacher for an example? Wouldn't it be simpler to just consider $X_i$ such that $P(X_i = -1)=1$? Also, doesn't $E(X_1) = E(X_2)$ follow from the iid assumption of the question? $\endgroup$
    – psarka
    Jan 5, 2018 at 16:22
  • $\begingroup$ @psarka, no particular reason, your example of $P(X_i=-1)=1$ would work too but I prefer non-deterministic random variables-they are more fun. For your second question, yes $\mathbb{E}(X_1)=\mathbb{E}(X_2)$ follows from the i.i.d. assumption.However, the point made by Zhanxiong in the comments is that the i.i.d. assumption is a stronger assumption than necessary to prove the claim. I was trying to show/argue how to show it without i.i.d. assumption. $\endgroup$ Jan 5, 2018 at 16:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.